The Potential Energy Curves and Spectral Constants of $Si_2N$ (Journal of Atomic and Molecular Sciences, 2022)
The equilibrium geometries of $Si_2N$ have been calculated using differentquantum chemistry calculation methods. Through a large number of test and research,the method QCISD/6-31G(2d,2p) is the most suitable for the calculation of $Si_2N$ bycomparing the experimental equilibrium structure and harmonic frequency data. Theforce constants have also been calculated. Based on the general principles of microscopicreversibility, the dissociation limits has been deduced. The analytical potentialenergy function of $Si_2N$ has been obtained based on the many-body expansiontheory. The potential surface graphs have been presented. It's found that there is aminimum value of 4.725eV at stable structure of the potential surface and a potentialwell of 1.7eV correspond to the linear asymmetric structures($^2Π).$ And the reactionof $SiN+Si → SiNSi$ based on the potential energy surface is discussed briefly, which issuccessfully used for describing molecular reaction dynamics.
Keywords: harmonic frequency; force constants; potential energy function.